THE EFFECT OF SELECTIVE SEROTONIN REUPTAKE INHIBITOR (SSRI) TREATMENT ON MEAN PLATELET VOLUME IN MAJOR DEPRESSIVE DISORDER (MDD) PATIENTS - Demircan, Fatih; Gozel, Nevzat; Kilinc, Faruk; Yilmaz, Musa; Donder, Emir; Atmaca, Murad (Carbone Editore, 2016)
Introduction: Patients with depression are at an increased risk for cardiovascular disease. Mean platelet volume (MPV) provides a measurement of activated platelets; increasing platelet activation is one of the mechanisms that may link depression and ischemic cardiac disease. Material and method: 100 newly diagnosed patients with major depressive disorder (MDD) and 100 healthy controls admitted to our outpatient clinics. We started selective serotonin reuptake inhibitor (SSRI) treatment in the MDD patients and followed them for 3 months. Patients' laboratory tests and physical, neurological, and psychiatric examinations were performed both at diagnosis and after 3 months of treatment. Results: The MDD group consisted of 90 people and the control group consisted of 88 people met the inclusion/exclusion criteria. There was no significant difference between the ages of the groups (p = 0.28). There were more males within the MDD group (55.6%). MPV was significantly greater in MDD group (p<0.001); MPV levels showed significantly decline after treatment with SSRIs (p<0.001). The platelet counts were also significantly low in MDD patients when compared with the control group, with the difference being statistically significant (p<0.001). No significant difference was observed in platelet counts after treatment. Severity of depression also declined after treatment. The average Montgomery-Asberg Depression Rating Scale (MADRS) score decreased 9.23 points; the difference was statistically significant (p<0.001). Conclusion: We conclude that MPV can be an indicator of platelet activity in patients with MDD and SSRIs can be used along with MPV to help identifying and treating coronary artery disease in MDD patients. According to our findings, SSRIs may have an antiplatelet action in addition to their antidepressant effects, which may be beneficial for MDD patients with coronary artery disease.
Keywords: Depression; mean platelet volume; coronary artery disease; SSRI